Improving the Quality of Life for the Elderly with Degenerative Diseases through to the Charitas Group Virtual Health Education Program during the Pandemic of the COVID-19 - Wilma Hannie Daniel; Chairil Anwar; Nur Alam Fajar; Rico Januar Sitorus; Ahmad Ghiffari (HM Publisher, 2021)
Background: In the era of the COVID-19 pandemic, various problems were experienced by the elderly, especially those with degenerative diseases, as the population most at risk of being exposed to COVID-19. The elderly are vulnerable to decreased physical, mental and social health; therefore, a new and effective strategy is needed to improve healthy living behavior in this population. This study aimed to analyze the effect of the Charitas Group virtual health education program on improving the quality of life of the elderly with degenerative diseases in the era of the COVID-19 pandemic. Methods: The One Group Pretest-Posttest Pre-Experimental study was with a sample of 33 patients selected by purposive sampling in May - July 2021. The data collection was taken using the World Health Organization Quality of Life – Bref (WHOQOL-Bref) form, translated and validated into Bahasa Indonesia. The data was then compared before and after the intervention and analyzed using the Paired Samples T-Test. Results: The T-Test showed a significant difference between the pre-test and post-test results (p-value 0.041 < 0.05). At the same time, the other T-Test results showed a significant influence on the quality of life of the elderly in the specific domains, namely: Psychological (p-value 0.025), Social Relationship (p-value 0.033) and Environmental (p-value 0.034). Conclusions: The Charitas Group virtual health education program significantly influences the quality of life of elderly people with degenerative diseases in the COVID-19 pandemic era.